Effect of bihemispheric transcranial direct current stimulation on distal upper limb function and corticospinal tract excitability in a patient with subacute stroke: a case study - Shiba, Takahiro; Mizuta, Naomichi; Hasui, Naruhito; Kominami, Yohei; Nakatani, Tomoki; Taguchi, Junji; Morioka, Shu (Frontiers in Rehabilitation Sciences, 2023)
Introduction Activation of the unaffected hemisphere contributes to motor function recovery post stroke in patients with severe upper limb motor paralysis. Transcranial direct current stimulation (tDCS) has been used in stroke rehabilitation to increase the excitability of motor-related areas. tDCS has been reported to improve upper limb motor function; nonetheless, its effects on corticospinal tract excitability and muscle activity patterns during upper limb exercise remain unclear. Additionally, it is unclear whether simultaneously applied bihemispheric tDCS is more effective than anodal tDCS, which stimulates only one hemisphere. This study examined the effects of bihemispheric tDCS training on corticospinal tract excitability and muscle activity patterns during upper limb movements in a patient with subacute stroke. Methods In this single-case retrospective study, the Fugl–Meyer Assessment, Box and Block Test, electromyography, and intermuscular coherence measurement were performed. Intermuscular coherence was calculated at 15–30 Hz, which reflects corticospinal tract excitability. Results The results indicated that bihemispheric tDCS improved the Fugl–Meyer Assessment, Box and Block Test, co-contraction, and intermuscular coherence results, as compared with anodal tDCS. Discussion: These results reveal that upper limb training with bihemispheric tDCS improves corticospinal tract excitability and muscle activity patterns in patients with subacute stroke.